Approach to pain management in oncology patients - Júnior, Délio Guerra Drummond; Maziero, Letícia Pirola; Frigheto, Fernanda Cristine; Ferreira, Gabriel Ayres; Chioveti, Gabriela Ricalde; Carvalho, Maria Isabella Ciaco de; Dutra, Giulia Valcanaia; Muniz, Júlia Zanusso Pontes; Carmo, Tiago Chave do; Santos, Daniel Aparecido dos; Pinheiro, Tiago Bruno Florencio (Seven Editora, 2024)
Introduction: The treatment of pain in cancer patients is an essential area to promote quality of life and well-being, relevant studies and articles on the management of pain treatment in cancer patients will be addressed, highlighting the methods, results. Methods: Several references related to the topic were analyzed, including longitudinal studies, reviews, and scientific articles. The selected sources cover different aspects of pain management in cancer patients, including pharmacological and non-pharmacological approaches, complementary therapies, palliative care, and integrative practices. The review of the articles allowed us to obtain a comprehensive and up-to-date view of the multidisciplinary approach in this context. Results: The results of the reviewed studies and articles point to the efficacy of the multidisciplinary approach in the treatment of pain in cancer patients. It was observed that the combination of pharmacological interventions, such as analgesics, with non-pharmacological approaches, such as occupational therapy, physiotherapy, and complementary therapies, showed better results in reducing chronic pain compared to conventional treatment. In addition, the inclusion of palliative care and integrative practices provided additional pain relief and improved quality of life for patients. Conclusion: A multidisciplinary approach to the treatment of pain in cancer patients is essential to provide comprehensive and effective care. This approach considers the individuality of patients, addressing physical, psychological, and social aspects of pain. Collaboration between healthcare professionals, including doctors, nurses, physiotherapists, psychologists, and pharmacists, is essential to ensure personalized treatment tailored to the needs of each patient. The use of complementary therapies and integrative practices, in conjunction with conventional approaches, has also been shown to be beneficial in reducing pain and increasing quality of life. In summary, the multidisciplinary approach shows promise and effectiveness in the treatment of pain in cancer patients, providing pain relief and improving the overall well-being of these individuals. DOI:https://doi.org/10.56238/sevened2024.001-034